2020
DOI: 10.1016/s2214-109x(20)30109-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and management of maternal infection in health facilities in 52 countries (GLOSS): a 1-week inception cohort study

Abstract: Background Maternal infections are an important cause of maternal mortality and severe maternal morbidity. We report the main findings of the WHO Global Maternal Sepsis Study, which aimed to assess the frequency of maternal infections in health facilities, according to maternal characteristics and outcomes, and coverage of core practices for early identification and management.Methods We did a facility-based, prospective, 1-week inception cohort study in 713 health facilities providing obstetric, midwifery, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 24 publications
4
81
0
5
Order By: Relevance
“…The median value and dispersion measures were computed for numerical variables, and proportions were calculated for categorical variables. For the items rated on a 9-point Likert scale, we measured the absolute and relative frequency in each of the three intervals: low (1-3), intermediate (4)(5)(6) and high (7)(8)(9). Each item was classi ed as inappropriate, uncertain or appropriate based on the median rating and degree of disagreement (median 1 to 3 without disagreement = inappropriate; median 4 to 6 or any median with disagreement = uncertain; median 7 to 9 without disagreement = appropriate).…”
Section: Resultsmentioning
confidence: 99%
“…The median value and dispersion measures were computed for numerical variables, and proportions were calculated for categorical variables. For the items rated on a 9-point Likert scale, we measured the absolute and relative frequency in each of the three intervals: low (1-3), intermediate (4)(5)(6) and high (7)(8)(9). Each item was classi ed as inappropriate, uncertain or appropriate based on the median rating and degree of disagreement (median 1 to 3 without disagreement = inappropriate; median 4 to 6 or any median with disagreement = uncertain; median 7 to 9 without disagreement = appropriate).…”
Section: Resultsmentioning
confidence: 99%
“…[16] Lo mismo fue observado en el Estudio Global de Sepsis Materna realizado por la OMS donde se encontró una menor proporción de infecciones maternas por cada 1000 nacimientos en los países desarrollados vs los no desarrollados. [17] Etiopatogénesis Durante el embarazo y postparto, la etiología de la sepsis (Ver tabla 1) puede ser resultado de condiciones obstétri cas o no obstétricas. [2] Los casos de sepsis en antepar to primordialmente son de origen no pélvico, mientras que los casos intraparto y postparto tienen más probabili dades de tener una fuente pélvica.…”
Section: Definicionesunclassified
“…Indeed, the global maternal sepsis study (GLOSS) was set up with one of its main objectives to develop and validate identi cation criteria for possible severe maternal infection and maternal sepsis [52]. This issue has been highlighted by the GLOSS group, following their recent study, where they stressed the urgent need to improve early identi cation of maternal sepsis [5].…”
Section: Main Ndingsmentioning
confidence: 99%
“…Pregnancy-related infections are also one of the leading causes of maternal and neonatal death globally [1][2][3][4]. The WHO Global Maternal Sepsis Study (GLOSS) Research Group has recently reported that Infection-related maternal deaths contributed to more than half of the intra-hospital deaths identi ed during their study period [5]. Although the prevalence of sepsis-related maternal mortality is much higher in low and middle-income countries (LMICs), sepsis in pregnancy is still one of the most important causes of maternal death in the developed world as well [6].…”
Section: Introductionmentioning
confidence: 99%